Lipid Profile Variations Across CKD Stages and their Association with Cardiovascular Risk: A Cross-Sectional Study - Mansoor Ali Baig; Saffalya Nayak; Debjyoti Mohapatra; Pratima Kumari Sahu; Prachi Pratichi Das; Jayanta Kumar Panda (Global Journal of Medicine and Public Health)
Background Chronic kidney disease (CKD) is a major global health concern associated with significant cardiovascular morbidity and mortality. Dyslipidemia, a hallmark of CKD, plays a critical role in cardiovascular disease (CVD) progression. This study evaluates lipid profile alterations and their association with cardiovascular risk across CKD stages. Methods This cross-sectional study included 95 patients with CKD from SCB Medical College and Hospital, Odisha, India. Participants were classified according to CKD stages 1–5 based on eGFR. Lipid profiles, including total cholesterol (TC), low density lipoprotein (LDL), high density lipoprotein (HDL), triglycerides (TG), and very low density lipoprotein (VLDL) were assessed using fasting blood samples. Cardiovascular risk was evaluated using the Framingham risk score. Statistical analyses included the Kruskal-Wallis test, Pearson’s correlation, and multivariate logistic regression. Survival probabilities were analyzed using Kaplan-Meier plots. Results HDL cholesterol declined significantly with CKD progression (p = 0.011), while total and LDL cholesterol levels were lower in Stage 5 (p = 0.002 and p = 0.031, respectively). Triglycerides and VLDL cholesterol showed positive correlations with cardiovascular risk (p = 0.006 and p = 0.005), whereas HDL cholesterol exhibited a negative correlation (p = 0.002). Multivariate regression identified low HDL cholesterol (OR: 0.88, p = 0.003) and elevated triglycerides (OR: 1.05, p = 0.01) as independent predictors of cardiovascular events. Kaplan-Meier analysis demonstrated declining survival rates with advancing CKD stages (log-rank p < 0.05). Conclusion Dyslipidemia significantly contributes to cardiovascular risk in patients with CKD. Targeted lipid management, particularly addressing HDL and triglycerides, may mitigate cardiovascular complications and improve outcomes in patients with CKD.